The impact of persistent anomalous precipitation in Southwest China caused by low-frequency atmospheric disturbances in different latitudes and altitudes - Xiao, Tian-Gui; Huang, Yao; Han, Lin; Nong, Ya-yue (Frontiers in Earth Science, 2023)
Previous studies have pointed out that persistent abnormal precipitation is closely related to atmospheric low-frequency oscillation, and Southwest China can be affected by low-frequency oscillation in different latitudes and altitudes. Therefore, it is necessary to study the relationship between persistent abnormal precipitation in Southwest China and low-frequency oscillation. In this study, the characteristics of atmospheric low-frequency oscillation in different latitudes and altitudes affecting persistent extreme precipitation in Southwest China were discussed by synthetic analysis and Butterworth filtering with precipitation data from meteorological stations and NCEP/NCAR reanalysis data, and the configuration relationship of low-frequency systems in three-dimensional space was shown. The results showed the following: 1) in the low-frequency circulation field, the Ural Mountains, east of Lake Baikal, the Sea of Okhotsk (Japan), the Western Pacific subtropical high control area, the South China Sea, the Indian Peninsula, and the Bay of Bengal were the key areas affecting precipitation; 2) oscillation could better reflect the original circulation characteristics at all latitudes of each layer, and on a period of oscillation of 15–30 days, it will affect precipitation at all altitudes and latitudes; and 3) at the lower level, different low-frequency cyclones and anticyclones moved to the mid-latitude and converged in different forms in the precipitation area. In the middle layer, the low-frequency high-pressure and low-pressure centers in the middle and high latitudes moved southward, finally forming a circulation situation of the high west and low east. At the upper level, the rainy area was controlled by low-frequency anticyclones and divergence centers from different regions, forming a high-altitude divergence field. The results can provide a theoretical basis for forecasting the extended period of persistent heavy rain in Southwest China.